STUDENTS' COMPETENCE IN TRANSFORMING ACTIVE VOICE TO PASSIVE VOICE AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF KHAIRUN UNIVERSITY - Jaya, Parwati; yetty, yetty; Ismail, Ade; Firmansyah, Firmansyah (Cakrawala Bahasa, 2025)
This study aims to investigate students’ competence in transforming active sentences into passive sentences and to identify the common errors frequently made in the process. A mixed-method approach, combining quantitative and qualitative methods, was employed in this research. The data were collected through a written test administered to 28 fourth-semester students from Class B of the English Language Education Study Program at Khairun University. The results revealed that the students’ average score was 51.25, which falls into the “poor” category. Furthermore, the analysis indicated several types of common errors made by students when transforming active sentences into passive ones. These include incorrect use of verb forms, tense formation errors, misuse or omission of prepositions such as “by”, and mistakes in placing agents or subjects within passive constructions. Among these, tense formation errors emerged as the most dominant problem, suggesting that many students lack a sufficient understanding of tense consistency when converting active sentences into passive forms. These highlight that students still lack a comprehensive understanding of the grammatical rules and syntactic structure involved in the process of transforming active sentences into passive ones. Therefore, mastery of passive transformation requires not only grammatical accuracy but also a deeper understanding of sentence logic and structure